Sleep and Fatigue Among Seafarers: The Role of Environmental Stressors, Duration at Sea and Psychological Capital - Sigurd W. Hystad; Jarle Eid (Elsevier, 2016)
Background: Seafaring is an inherently stressful environment. Because working time and leisure time is spent in the same confined environment for a prolonged period of time, many stressors present in seafaring can also be conceived of as chronic. We explored the effects of duration at sea, seafaring experience, environmental stressors, and psychological capital (PsyCap) on the sleep quality and fatigue of seafarers. PsyCap is a construct that draws upon ideas from positive psychology and positive organizational behavior, and is intended to capture an individual's psychological capacities that can be developed and utilized for performance improvements. Methods: We collected survey data from a sample of seafarers working in the offshore re-supply industry (n=402) and a sample of seafarers working on board combined passenger and cargo ships (n=340). Results: PsyCap emerged as a robust predictor with statistically significant relations to fatigue and sleep quality in both samples. PsyCap also interacted with duration at sea in explaining fatigue in seafarers working on board the passenger and cargo ships. Seafarers on passenger and cargo ships also reported significantly higher levels of fatigue than those working in the offshore re-supply industry. Conclusion: Coupled with emerging research showing that PsyCap is trainable, our results suggest that maritime organizations could have much to gain by being cognizant of and developing routines for continually developing the PsyCap of their employees.